Detecção de Indisponibilidades em Aplicações Web - Schulz, Daniel; Marotta, Marcelo; Bondan, Lucas; Rocha Filho, Geraldo P.; Caetano, Marcos; Araujo, Aleteia (Anais da Escola Regional de Alto Desempenho do Centro-Oeste (ERAD-CO); 2023: Anais da VI Escola Regional de Alto Desempenho do Centro-OesteDO - 10.5753/eradco.2023.234679, 2023)
The internet's growth transformed business services but also brought challenges with failures in Information Systems. Stable operations require continuous monitoring aligned with ITIL. This study suggests a novel method, applying data mining for rapid failure detection. It evaluates real-time web analytics data to swiftly identify critical web app failures. Preprocessing and hyperparameters were optimized using hyperopt for improve accuracy. Seven models were made; LSTM excelled, validating its effectiveness in differentiating failures from successes.